Electrochemically driven generation of manganese(IV,V)-oxo multiporphyrin arrays and their redox properties with manganese(III) species in Langmuir-Blodgett films - Zhang, Chao-Feng (Langmuir : the ACS journal of surfaces and colloids, 2008)
High-valency manganese (IV,V)-oxo porphyrins have been electrochemically generated and in situ spectrally characterized in multiporphyrin arrays, which were formed by an interfacial coordination reaction of Na2PdCl4 with manganese (III) tetrapyridylporphyrin (MnTPyP). Multilayers of the Pd-MnTPyP multiporphyrin arrays were obtained by the Langmuir-Blodgett (LB) method. The redox behaviors of manganese in the multiporphyrin arrays were pH-dependent. Spectroelectrochemical experiments revealed a reversible redox process between Pd-Mn(III)TPyP and its Mn(IV)-oxo species, but an irreversible process between Pd-Mn(III)TPyP and its Mn(V)-oxo species. The Pd-Mn(IV)TPyP multiporphyrin arrays could be spontaneously reduced to their Mn(III) complex, while the Pd-Mn(V)TPyP arrays were rather stable in basic solutions (pH > 10.5). However, when the Pd-Mn(V)TPyP multiporphyrin arrays were washed by or immersed in water, they were immediately reduced to their Mn(III) complex. Because these well-organized multiporphyrin arrays are of high thermal and chemical stability, they are potential molecular materials in the studies of natural and artificial catalytic processes as well as redox-based molecular switches